A probable case of poliomyelitis imported to Malaysia - Tay, C.G.; Ong, L.C.; Goh, K.J.; Rahmat, K.; Fong, C.Y. (Elsevier, 2015)
We report a previously well 10-month-old Somalian girl who acquired asymmetric lower limb weakness in July 2013 in Mogadishu, Banadir, before arriving in Malaysia at 12 months of age. In May 2013, there was a wild poliomyelitis outbreak in that area, as reported by the World Health Organization. Laboratory investigation, including cerebrospinal fluid, was unremarkable, and electrophysiological studies showed active axonal denervation in the left lower limb. The whole spine T2-weighted MRI revealed non-enhancing hyperintensities of the bilateral anterior horn cells, predominantly on the left side at T11-12. The viral isolations from two stool specimens at her presentation to our centre, 2 months after the onset of illness and 2 weeks apart, were negative. Despite lacking the acute virological evidence of poliomyelitis, in view of the girl's clinical, electrophysiological and classical spinal neuroradiological features, together with her temporal relationship with a World Health Organization reported wild poliomyelitis outbreak, we believe these findings are consistent with a diagnosis of imported poliomyelitis. A review at 30 months of age showed persistent left lower limb monoplegia with little recovery. Our patient reiterates the importance of maintaining awareness of wild polio importation, and keeping abreast of the latest news of global poliomyelitis outbreaks when treating patients with flaccid paralysis, even if they arrive from non-endemic poliomyelitis areas.